PENGARUH KOTA PALU SEBAGAI PUSAT PERTUMBUHAN TERHADAP PERTUMBUHAN EKONOMI WILAYAH HINTERLAND - Ramlah, Miranti Widya (Katalogis, 2017)
The study aims to analyze the influence of Palu City as a center of growth towards the economic growth of Parigi Moutong District, Donggala District, and Sigi District as buffer zones of Palu City. The study also seeks the performance of the rapidly growing pre-eminent sectors in Palu City that affects the growth of the economic sectors in the hinterland regions. Data collecting method uses literature study on secondary data based on PDRB per capita of province and districts in Central Sulawesi. The results find that: 1) based on the completeness of the infrastructure and effectiveness of the coverage of infrastructure services,Palu City is defined a growth center and ParigiMoutong Districts, Donggala District, and Sigi District as its buffer zones; 2) based on Gravity Analysis, Donggala District is a hinterland area that has the closest spatial interaction with the growth center; 3) based on shift share analysis, it reveals that the leading sector in Palu City indirectly influences the economic growth in the region.